The Interplay of Content and Community in Synchronous and Asynchronous Communication: Virtual Communication in a Graduate Seminar - Richard A. Schwier; Shelly Balbar (The Canadian Network for Innovation in Education (CNIE), 2002)
A group of graduate students and an instructor at the University of Saskatchewan experimented with the use of synchronous communication (chat) and asynchronous communication (bulletin board) in a theory course in Educational Communications and Technology for an eight-month period. Synchronous communication contributed dramatically to the continuity and convenience of the class, and promoted a strong sense of community. At the same time, it was viewed as less effective than asynchronous communication for dealing with content and issues deeply, and it introduced a number of pedagogical and intellectual limitations. We concluded that synchronous and asynchronous strategies were suitable for different types of learning, and what we experienced was a balancing act between content and community in our group. A combination of synchronous and asynchronous experiences seems to be necessary to promote the kind of engagement and depth required in a graduate seminar.